DETERMINATION OF THE WORKING ENVIRONMENT, COMPETENCY AND COMMUNICATION ON EMPLOYEE ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS INTERVENING VARIABLE IN THE RIAU ISLAND PROVINCE HEALTH DEPARTMENT - Lestari, Citra; Wibisono, Chablullah; Khaddafi, Muammar; Indrayani, Indrayani (RADJA PUBLIKA, 2022)
This study aims to determine the determination of the work environment, competence, communication on work commitment and job satisfaction as intervening variables. The hypothesis proposed that Work Environment determines Job Satisfaction, Competence determines Job Satisfaction, Communication determines Job Satisfaction, Work Environment determines Work Commitment, Competence determines Work Commitment, Communication determines Work Commitment, Job Satisfaction determines Work Commitment, Work Environment determines Work Commitment through Job Satisfaction, Competence determines work commitment through job satisfaction, communication determines work commitment through job satisfaction. The sample in this study were all employees of the Riau Islands Province Health Service with the status of ASN. The number of samples used is 119 respondents. The data obtained were analyzed using data analysis techniques with the help of AMOS 24.0 software. The results of the study show that the work environment determines job satisfaction. CR value of 3.035 > 2,000 and Probability = 0.002 < 0.05, indicating that the positive determination is significant. Competence on Job Satisfaction CR value of 3,641 > 2,000 and Probability = ***<0.05, indicating that the positive determination is significant. Communication on Job Satisfaction Value of CR = 2.330 > 2,000 and Probability = 0.02 <0.05 indicates that the positive determination is significant. Work Environment on Work Commitment Value of CR -0.144 < 2,000 and Probability 0.886 > 0.05 indicates that the positive determination is not significant. Competence on Work Commitment. CR value 0.190 < 2, 000 and Probability = 0.849 > 0.05 indicates that the positive determination is not significant. Communication on Work Commitment Value of CR 1.901 < 2,000 and Probability = 0.057 > 0.05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. 05 indicates that the positive determination is not significant. Communication on Work Commitment Value of CR 1.901 < 2,000 and Probability = 0.057 > 0.05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. 05 indicates that the positive determination is not significant. Communication on Work Commitment Value of CR 1.901 < 2,000 and Probability = 0.057 > 0.05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. Communication on Work Commitment Value of CR 1.901 < 2,000 and Probability = 0.057 > 0.05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. Communication on Work Commitment Value of CR 1.901 < 2,000 and Probability = 0.057 > 0.05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. 05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. 05 indicates that the positive determination is not significant. Job Satisfaction on Work Commitment CR value 0.503 < 2,000 and Probability = 0.615 < 0.05 indicates that the positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant. Determination of Work Environment on work commitment through job satisfaction 0.34202342 > 0.005 indicates that positive determination is not significant. Determination of competence on work commitment through job satisfaction 0.3349426 > 0.005 indicates that positive determination is not significant. Communication determination on work commitment through job satisfaction 0.35833489 > 0.005 indicates that positive determination is not significant.